Supervision and Trust in Work Involvement Through the Role of Work Motivation at Simpang Lima Gumul Hospital, Kediri - Eni Rohma Wiyati; Joko Prasetyo; Ratna Wardani (Fakultas Ekonomi Universitas Kadiri, 2023)
This study aimed to analyze the effect of work motivation as a mediating variable from Supervision and trust on work involvement in Simpang Lima Gumul Hospital, Kediri. The location in this study was carried out at the Simpang Lima Gumul Hospital, Kediri. The objects in this study were work motivation, Supervision, Trust, and work involvement of the employees of Simpang Lima Gumul Hospital, Kediri. As for the research object, the independent variable is Supervision and Trust as variable X, the dependent variable is work involvement as variable Y, and the mediating variable is work motivation as variable Z. Meanwhile, the subject in This research is a health worker in Simpang Lima Gumul Hospital, Kediri. The population used as the object of this research was the health workers of Simpang Lima Gumul Hospital, Kediri, totaling 380 people. The sample in this study were Simpang Lima Gumul Kediri Hospital employees, namely employees who provide services to patients. Using the Krejcie and Morgan tables, the total population (N) was 380, so the sample (n) required was 191 people. This study uses Proportionate Stratified Random Sampling, which is used when the population has members who are not homogeneous and proportionally stratified. Based on the results of the analysis using smart-pls, it was found that Supervision has no significant effect on work involvement, Trust has a significant effect on work involvement, Work motivation has a significant effect on work involvement, Trust has no significant effect on work motivation, Supervision has a significant effect on work motivation, Motivation mediates the effect of Supervision on work involvement, Motivation mediates the effect of Trust on work involvement.